Worthy both In character and learning: The Adeleke University advantage (2025)
The prospects of earning a good degree at the end of an undergraduate programme, which for the purpose of our discourse here is either a First Class or a Second Class Honours (Upper Division), is a major criterion that students use in selecting their preferred University. In this paper, we compare the graduate output in 12 selected Universities in Nigeria, comprising six public universities and six private universities with the United Kingdom average. In the UK, about 31% of the students graduate with First Class. The comparative figures in the 12 Nigerian Universities are much lower. Moreover, the typical class of degree in the UK is Second Class Upper which is similar to what obtains in the selected Nigerian private universities. On the other hand, the typical degree in the selected Nigerian public universities is a Second Class (Lower Division). The graduating students of the Class of 2025 have acquired academic knowledge at the university level over the previous years of studentship at Adeleke University, Ede. As you leave here and move on to very great lofty things in your career, you would need to further sharpen your technical and soft skills, including but not limited to communication, curiosity, critical thinking, critical listening, empathy, teamwork, collaboration and negotiation skills, and industry awareness which are becoming increasingly important for leadership and work. University graduates can acquire various certifications to enhance their skills and employment prospects. These include Information Technology Certifications; Professional Certifications; Soft Skills Certifications; Industry-Specific Certifications; Project Management and Human Resources Certifications. Such certifications can demonstrate expertise, enhance job prospects, and increase earning potential. It is essential for new graduates to research certifications relevant to their field, passion and career goals. In the journey of life, I charge you all to engage in continuous professional development. You will do well to improve on your soft and entrepreneurial skills. If things do not work as envisaged, you should be resilient with a high adversity quotient.